A literature review: Entrustable professional activities, an assessment tool for postgraduate dental training?. (May 2022) - Kelly, Grace M.; Roberts, Anthony; Lynch, Christopher D.
Abstract: Assessing when dental trainees are ready to independently undertake clinical procedures at specialist level is critical for dental postgraduate programmes to determine when a trainee is 'work ready', in addition to ensuring patient safety. Entrustable professional activities (EPA) are a novel method of competency-based assessment. An EPA is a unit of professional practice or critical clinical activity identified within dental training programmes, which should be assessed during training, to establish if trainees are ready for independent practice, with a progressive decrease in supervision, based on supervisors' entrustment decisions. This article describes EPAs, entrustment decisions, including entrustment supervision scales and the process recommended to develop EPAs within dental curricula. EPAs have not been formally introduced for assessment within dental education programmes in the United Kingdom, but recent developments have been described in undergraduate dental education globally. Clinical significance: Competency-based assessments need to be continually developed to adapt to rapidly changing population health care and dental needs, to determine when dental trainees are ready for independent clinical practice. Early development of entrustable professional activities for assessment in undergraduate dental programmes has been well received by both trainees and supervisors. Further investigation is required to consider formal development of EPAs within postgraduate dental programmes.